2021
DOI: 10.1212/wnl.0000000000012884
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Understanding MS Mechanisms and Progression With MRI Using Large-Scale Data Sharing and Artificial Intelligence

Abstract: Multiple sclerosis (MS) patients have heterogeneous clinical presentations, symptoms and progression over time, making MS difficult to assess and comprehend in vivo. The combination of large-scale data-sharing and artificial intelligence creates new opportunities for monitoring and understanding MS using magnetic resonance imaging (MRI).First, development of validated MS-specific image analysis methods can be boosted by verified reference, test and benchmark imaging data. Using detailed expert annotations, art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…However, these techniques may affect the succeeding image analysis. Consequently, protecting patients’ privacy while collecting their information continues to be a major challenge that needs to be addressed appropriately [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques may affect the succeeding image analysis. Consequently, protecting patients’ privacy while collecting their information continues to be a major challenge that needs to be addressed appropriately [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, machine learning and deep learning techniques have been successfully employed for a variety of tasks, including lesion and brain tissue segmentation, analysis of different MRI data modalities, differential diagnosis with other white matter disorders and disease prognosis. ( Vrenken et al, 2021 ) To date, most of studies applying AI to MRI data in MS used T2- and T1-weighted imaging, or advanced structural MRI techniques, such as susceptibility-weighted and diffusion-weighted imaging. ( Vrenken et al, 2021 , Moazami et al, 2021 ) Nevertheless, recent investigations showed promising results also when applying AI to fMRI data.…”
Section: New Perspectives For Fmri Analysismentioning
confidence: 99%
“…( Vrenken et al, 2021 ) To date, most of studies applying AI to MRI data in MS used T2- and T1-weighted imaging, or advanced structural MRI techniques, such as susceptibility-weighted and diffusion-weighted imaging. ( Vrenken et al, 2021 , Moazami et al, 2021 ) Nevertheless, recent investigations showed promising results also when applying AI to fMRI data. For instance, Saccà et al ( Saccà et al, 2019 ) applied five different machine learning techniques to maps of the sensorimotor network (reconstructed by independent component analysis) in 18 people with early MS and 19 HC.…”
Section: New Perspectives For Fmri Analysismentioning
confidence: 99%
“…AI and large-scale data sharing could easily predict the progression of MS, which is crucial for treatment planning and optimizing patient outcomes [ 61 , 62 ]. It covers a large field from MRI image analysis “T2-fluid-attenuated inversion recovery (FLAIR), 2D T1-weighted images (WI), 3D T1-WI, diffusion tensor imaging, and functional magnetic resonance imaging” to large multidomain datasets [ 61 , 63 ].…”
Section: Reviewmentioning
confidence: 99%